Uncertainty evaluation for determination of 14C in urine samples by wet oxidation method - Linlin Yan; Xiao Ge; Qiang Xiong; Fei Chen; Jing Liang; Zhen Zhang; Shengyuan Yang (Radiation Medicine and Protection, 2021)
Objective: To figure out the source of uncertainty in the determination of 14C activity concentration in urine samples, and to establish a complete expression of analysis results, in order to improve the accuracy of 14C monitoring method. Methods: Four urine samples of normal people were collected, and wet oxidation method was used in the pretreatment of the samples, then the activity concentration of 14C was determined by liquid scintillation counting (LSC). After the mathematical model was established, the uncertainty components were determined, the standard uncertainty was combined, and the extended uncertainty was calculated. Results: The relative uncertainty of 4 samples was 22.5%, 17.0%, 17.3% and 18.2%. The activity concentration of urine was (0.32 ​± ​0.14), (0.60 ​± ​0.20), (0.86 ​± ​0.30) and (0.74 ​± ​0.27) Bq/L, respectively. In the relative uncertainty of 22.5%, 17.7% was from sample counting, 13.6% from detection efficiency, 2.1% from recovery rate, 0.58% from sample volume, and 0.01% from sample weight. Conclusions: The main factors affecting the uncertainty include the error or deviation of sample counting, detection efficiency and recovery rate. The error of volume and weight also contributes to the measurement uncertainty.